The influence of production mechanisms on pick‐up ion loss at Mars. Issue 1 (31st January 2013) - Curry, S. M.; Liemohn, M.; Fang, X.; Ma, Y.; Espley, J.
Abstract : [1] This study quantifies the influence of ionization production mechanisms on ion escape and transport through near‐Mars space. The Mars Test Particle simulation calculates the detailed ion velocity space distribution through a background magnetic and electric field model at specific locations. The main objective of this work is to extensively probe the sources of O + ion escape relative to the production mechanisms: photoionization, charge exchange, and electron impact. Seven production methods are explored and compared, resulting in total production and loss rates differing up to two orders of magnitude. Photoionization was compared as a function of solar zenith angle and optical shadow. Charge exchange O + production was studied with three methods: a constant rate assuming cold ion collisions, a constant rate proportional to the reaction cross‐section and upstream solar wind bulk velocity, and finally a novel approach proportional to the cross‐section and both the random and bulk velocity. Finally, electron impact ionization was considered as a constant and as a function of electron temperature. Of these methods, a baseline of the most physically relevant ion mechanisms was selected. Additionally, energy distributions at specific spatial locations highlight the individual ion populations in velocity space, revealing asymmetric and nongyrotropic features due to specific ionization methods. Analysis of the O + flux and loss is in agreement with observations and also indicates a strong polar plume in the northern hemisphere for a given interplanetary magnetic field orientation. We calculate the total production and escape to be 2.5 × 10 25 and 6.4 × 10 24, respectively. Key Points: 4B test particles permit the examination of pick-up ion flux distributions Ion production rates are critical to escape- can change 2 orders of magnitude Total O+ escape is 6.4e24 per sec